2012
DOI: 10.1016/j.jphotobiol.2012.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-sensitized UVA induced apoptosis in human keratinocytes through mitochondrial oxidative stress and pore opening

Abstract: Resveratrol (3, 5, 4′-trihydroxy- trans- stilbene), a polyphenol compound, is derived from natural products such as the skin of red grapes, blueberries and cranberries. Resveratrol not only exhibits antioxidant, cardioprotection, and anti-aging properties, but can also inhibit cancer cell growth and induce apoptosis. It has been shown that resveratrol inhibits the activation of Nf-kB and subsequently down regulates the expression of Nf-kB regulated genes such as interleukin-2 and Bcl-2, leading to cell cycle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
1
26
1
1
Order By: Relevance
“…Resveratrol is a natural compound found in grapes, blueberries and cranberries, which has been reported to have anti-tumor properties due to its ability to induce apoptosis and cell cycle arrest [5]. Previous work has confirmed that resveratrol can inhibit the proliferation of human MM cell lines and alter the population of S phase [6].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is a natural compound found in grapes, blueberries and cranberries, which has been reported to have anti-tumor properties due to its ability to induce apoptosis and cell cycle arrest [5]. Previous work has confirmed that resveratrol can inhibit the proliferation of human MM cell lines and alter the population of S phase [6].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of RSV and arsenite increased apoptotic cancer cell death through generation of OS. A report deals with OS in eye cells of diabetic rats involving an increase in OS (Boyer, Jandova, Janda et al, 2012). Protein carbonyl content was increased and GSH levels were decreased.…”
Section: Resveratrol (Rsv)mentioning
confidence: 99%
“…Exposure of skin to UV-A generates large quantities of intracellular ROS, which directly or indirectly affect various cell signaling pathways, including oxidative stress and apoptosis (Fu et al 2000). In addition, oxidative stress mediates various UV-induced cutaneous reactions, including inflammation, photosensitivity, and carcinogenesis (Boyer et al 2012;Narayanapillai et al 2012). These effects attributed to UV-A irradiation are also associated with generation of ROS including singlet oxygen ( 1 O 2 ), superoxide radicals (O 2 ¡ ), hydrogen peroxide (H 2 O 2 ), hydroxyl radicals (OH), and nitric oxide (NO), and these ROS were found to induce various biological processes, including apoptosis or programmed cell death such as mitochondrial oxidative stress (Boyer et al 2012) or DNA damage (Hseu et al 2012).…”
mentioning
confidence: 99%
“…In addition, oxidative stress mediates various UV-induced cutaneous reactions, including inflammation, photosensitivity, and carcinogenesis (Boyer et al 2012;Narayanapillai et al 2012). These effects attributed to UV-A irradiation are also associated with generation of ROS including singlet oxygen ( 1 O 2 ), superoxide radicals (O 2 ¡ ), hydrogen peroxide (H 2 O 2 ), hydroxyl radicals (OH), and nitric oxide (NO), and these ROS were found to induce various biological processes, including apoptosis or programmed cell death such as mitochondrial oxidative stress (Boyer et al 2012) or DNA damage (Hseu et al 2012). ROS were induced by UV photo-irradiation of some photosensitizers in a medium containing fatty acids and vitamins (Regensburger et al 2012) and cytoplasmic urocanic acid, riboflavin, and b-nicotinamide adenine dinucleotide (NAD) (Baier et al 2006).…”
mentioning
confidence: 99%